KKL DAN PROBLEM PEMANFAATAN MEDIA DALAM PEMBENTUKAN JARINGAN DAKWAH DI KALIMANTAN BARAT - Yusriadi, Yusriadi; Mujiono, Mujiono (Jurnal Al-Hikmah: Jurnal Dakwah, 2023)
The study, entitled "KKN and problems of media use in the formation of da'wah networks in West Kalimantan", aims to examine the various obstacles encountered in the utilisation of media in the context of practical work lectures (Kuliah Kerja Lapangan-KKL) with the objective of forming and reinforcing da'wah networks within the region. This study employs a documentary analysis approach, whereby a range of documents, reports, articles, and studies pertaining to the utilisation of media in the context of Da'wah in West Kalimantan were collated and subjected to rigorous examination. Interviews were also conducted to explore and deepen the necessary information about the KKL-DR 2021 activities. The findings revealed that several significant challenges impede the effectiveness of media utilisation in KKL and the establishment of Da'wah networks. These include a dearth of adequate technological infrastructure in some remote locations, as well as a paucity of digital literacy among students and the general public.  Furthermore, the absence of governmental and institutional backing, coupled with the challenge of maintaining consistency and sustainability of the programme through the network, represents an additional obstacle. It is recommended that improvements be made to the technological infrastructure, that digital literacy training be provided for students and the community, and that Da'wah content be developed that is more creative and relevant to the needs.Kajian yang bertajuk "KKL dan problem pemanfaatan media dalam pembentukan jaringan dakwah di Kalimantan Barat" ini bertujuan untuk mengkaji berbagai kendala yang dihadapi dalam pemanfaatan media dalam rangka kuliah kerja lapangan (KKL) dengan tujuan membentuk dan memperkuat jaringan dakwah di wilayah tersebut. Penelitian ini menggunakan pendekatan analisis dokumenter, dimana berbagai dokumen, laporan, artikel, dan kajian yang berkaitan dengan pemanfaatan media dalam konteks Dakwah di Kalimantan Barat. Wawancara juga dilakukan untuk menggali dan mendalami informasi yang diperlukan seputar kegiatan KKL-DR 2021. Temuan ini mengungkapkan bahwa beberapa tantangan signifikan menghambat efektivitas pemanfaatan media di KKL dan pembentukan jaringan Dakwah. Ini termasuk kelangkaan infrastruktur teknologi yang memadai, serta kurangnya literasi digital di kalangan mahasiswa dan masyarakat umum.  Selain itu, tidak adanya dukungan pemerintah dan kelembagaan, ditambah dengan tantangan untuk menjaga konsistensi dan keberlanjutan program melalui jaringan. Disarankan untuk dilakukan perbaikan infrastruktur teknologi, pemberian pelatihan literasi digital bagi mahasiswa dan masyarakat, serta pengembangan konten dakwah yang lebih kreatif dan relevan dengan kebutuhan